Pengembangan Website Kampung Batik Jetis Dengan Metode Rational Unified Process - Rizal Joko Hidayatullah; Niken Hendrakusma Wardani; Adhitya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Kampung Batik Jetis is one of the tourist village located in Sidoarjo regency. However, tourists who visit the Sidoarjo regency is less knowing of the existence of the village. Therefore, there are emerging needs of the village of batik, which currently do not have a profile web-based information portal with the purpose of showing all information for the public. Website development is done by using Rational Unified Process method. This method allows to systematically control the changes that occur in the software during the development process. Website development use object-oriented analysis and design approach where each requirement is grouped in several objects. Diagrams used include use case diagrams, activity diagrams, sequence diagrams and class diagrams. The test was performed using black box testing method and white box testing method. The solution for the lack of media introduction Kampung Batik Jetis one of which is the development of a website profile. Black box testing results using the use case testing techniques of 18 features tested entirely valid. While testing with white box testing method with basis path testing techniques resulting in three valid test results. The expected results with the website profile, residents, especially craftsmen Kampung Batik Jetis can promote the village to the maximum.